Corporate communication - Argenti, Paul A. (McGraw Hill, 2023)
"This book grows out of more than 35 years of work developing the field of study referred to in this book as corporate communication. Although the term itself is not new, the notion of it as a functional area of management equal in importance to finance, marketing, human resources (HR), and information technology (IT) is more recent. In the past 35 years, senior managers at a growing number of companies have come to realize the importance of an integrated communication function"--